Preparation and anti‐leakage properties of sesbania gum‐grafted copolymers. Issue 13 (22nd October 2020) - Liu, Xiaomei; Cheng, Sha; Zhao, Junji; Qiu, Xueyan; Zhang, Wenxu; Ma, Guofu; Lei, Ziqiang
Abstract: A sesbania gum‐g‐poly (acrylic acid‐co‐vinyl acetate) (SG‐g‐P (AA‐co‐VAc)) emulsion was prepared by free radical polymerization using environmental‐friendly sesbania gum (SG) as raw material and grafted with acrylic acid and vinyl acetate. It was applied to study the performance of preventing water leakage from the soil. The effects of acrylic acid/vinyl acetate (AA/VAc) monomer ratio, neutralization degree of AA, content of ammonium persulfate and polymerization temperature on the properties of emulsion were investigated. Characterization of the emulsion by FTIR, SEM, TGA, and particle size distribution showed that AA and VAc were successfully grafted onto SG. SG‐g‐P (AA‐co‐VAc) had good stability under the optimum synthesis condition. Compared to SG, the thermal stability of the product was improved. The consolidation layer was formed after the product was added to the soil, which might reduce the voids between soil particles and reduce the water penetration rate. This greatly expanded its application in the research of anti‐leakage performance. Abstract :